Dupilumab for atopic dermatitis treatment: A single-center retrospective study - Gülbin Yaşar; Aslı Bilgiç; Ertan Yılmaz (Turkderm Turkish Archives of Dermatology and Venereology, 2022)
Background and Design: Atopic dermatitis (AD) is a common chronic, recurrent, and itchy inflammatory skin disease. Various therapeutic agents are available, but severe side effects may limit their usage. Recently, dupilumab, a human monoclonal antibody that targets the interleukin-4 (IL-4) receptor alpha subunit of heterodimeric IL-4 and IL-13 receptors, is approved and might be used in patients with resistant AD, with the permission of the Ministry of Health. Materials and Methods: This study aimed to retrospectively evaluate the clinical characteristics of patients and dupilumab treatment responses in our center. This study included patients with AD who were unresponsive to conventional treatments and treated with dupilumab. Sociodemographic, laboratory data, previous treatments, and responses along with disease severity scores [eczema area and severity index (EASI)] before and after dupilumab were evaluated through the electronic files of patients. Results: A total of 21 patients (13 males and 8 females) between June 2019 and March 2021 were identified. The mean age of patients was 40.57±15.21 years. The mean duration of dupilumab treatment was 6.59±5.88 months. The mean EASI score at the beginning of dupilumab was 15.35±8.03, whereas 4.6±2.9 after treatment. A 70-100% improvement was found in approximately 75% of the patients. No side effects were observed that required treatment discontinuation or dose changes. Conclusion: Our study has the highest number of reported patients in our country, which revealed that dupilumab is highly effective and safe for conventional treatment-resistant AD.